457 The Effect of Biochemical Adversity of Primary Hyperparathyroidism on Preoperative Imaging (SPECT-CT and US Parathyroids). (12th October 2021) - Durand, C; Anderson, H; Simpson, D; Gull, S; Oprean, R; Lim, K; Lee, F; Kakos, C; Cvasciuc, T
Abstract: Aim: Primary hyperparathyroidism (PHPT) is a common endocrine disorder, with an estimated incidence of 1/500 women and 1/2000 men older than 40 years. Several factors influence the positivity of preoperative scans including serum calcium, PTH and vitamin D levels, and gland size. The aim of our study is to examine the effect of biochemical adversity of primary hyperparathyroidism on preoperative imaging (SPECT-CT and US parathyroids). Method: Retrospective study of 176 parathyroidectomies (2017-2020) in a tertiary referral centre with biochemistry, SPECT-CT, US parathyroids and histology outcomes being recorded. Failed parathyroidectomies were excluded. Results: Patients were divided into 4 groups based on the preoperative calcium levels (normocalcemia <2.6, 3.4%; mild 2.60-2.79, 51.1%; moderate 2.80-2.99, 31.2%; severe >3.0 mmol/l, 14.2% of patients). Age (p-0.0297), preoperative vitamin D (p-0.03) and PTH levels (p-0.0001) were different while SPECT-CT positivity (p-0.29) weight of gland (p-0.015) and US positivity (p-0.09) were similar within the subgroups. Looking at the whole group, patients with positive SPECT-CT have a larger weight (p < 0.0001) while preoperative PTH levels was higher for the positive SPECT-CT patients (p-0.0289). No relation was identified between calcium levels and SPECT-CT positivity (p-0.18). No significance between preoperative vitamin D and positivity of US and SPECT-CT within the study group were noted. Conclusions: Serum PTH levels and weight of the gland are directly correlated with positivity of preoperative imaging. Preoperative calcium and vitamin D levels correlates indirectly with the severity of the disease but did not influence the preoperative imaging positivity.